The impact of Covid-19 pandemic on Malaysian senior citizens: A review - Khairul Hanim Pazim@Fadzim; Roslinah Mahmud; Lim, Beatrice Fui Yee; Noor Fzlinda Fabeil; Juliana Langgat; Norhayati Ayob; Mohdnorazmi Nordin (International Journal of Aquatic Science, 2021)
In Malaysia, the presence of more aggressive variants with higher infectivity has influenced the decision to enforce the nationwide total lockdown on June 1, 2021 under the third Movement Control Order (MCO 3.0). Based on the overall fatality of COVID-19 statistics, studies have found that risk for severe illness with COVID-19 increases with age, with older adults and patients with comorbidities are more likely to have a more severe course of disease and a higher chance of death compared to other age groups. The impact of COVID-19 on this vulnerable group is likely to be multifaceted; disruptions in socioeconomic, health, sociocultural, and familial intergenerational support are expected to be important components impacted that are specific to Malaysia when compared to other nations. Furthermore, many older Malaysians may be reliant on their children for support, which could complicate matters further, particularly during a lockdown when visits are limited. Finally, the growing importance of digital platform use among the elderly is an issue that should be addressed. The goal of this article is to analyse the influence of the COVID-19 on older people in the context of exploring the prospects for their social and economic independence, emphasizing the importance of promoting efficient supports and networks to ensure the well-being of these vulnerable older people during a pandemic.